2013
DOI: 10.1007/s10792-013-9718-6
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of human leukocyte antigens in Eales disease and tuberculosis

Abstract: To analyze the association between Eales disease, histocompatibility leukocyte antigen alleles (HLA-A/B, HLA-DRB/DQB) and tuberculosis infection, and to explore susceptible genes and protective genes associated with Eales disease and tuberculosis infection in a population of Han nationals from Zunyi City in Guizhou Province, China. The subjects were analyzed by a case-control study consisting of three groups--Eales disease group (47 cases), pulmonary tuberculosis group (36 cases) and normal control group (100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Furthermore, its association with Mycobacterium tuberculosis, Mycobacterium fortuitum, and Mycobacterium chelonae exposure has been reported, causing a retinal autoimmune response [4,5]. Studies have shown that the tuberculin skin test (TST) was positive in 64% of patients suffering from Eales' disease [6]. In addition, individuals predisposed to HLA (HLA B5, DR1, DR4) are more likely to have an autoimmune response, due to tissue damage caused by mycobacterial antigen [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, its association with Mycobacterium tuberculosis, Mycobacterium fortuitum, and Mycobacterium chelonae exposure has been reported, causing a retinal autoimmune response [4,5]. Studies have shown that the tuberculin skin test (TST) was positive in 64% of patients suffering from Eales' disease [6]. In addition, individuals predisposed to HLA (HLA B5, DR1, DR4) are more likely to have an autoimmune response, due to tissue damage caused by mycobacterial antigen [5].…”
Section: Discussionmentioning
confidence: 99%
“…If presentation of Eales’ disease is unilateral, it is recommended to start treatment with periocular or intravitreal depot corticosteroids (triamcinolone acetonide or dexamethasone) to reduce the side effects of long-term systemic corticosteroids [ 6 ]. Systemics steroids (usually 1 mg/ kg body weight per day) are used in bilateral or severe cases to minimize the site of inflammation in Eales’ disease [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation